2015
DOI: 10.1038/srep08856
|View full text |Cite
|
Sign up to set email alerts
|

Src inhibitor reduces permeability without disturbing vascularization and prevents bone destruction in steroid-associated osteonecrotic lesions in rabbits

Abstract: To examine the therapeutic effect of Src inhibitor on the VEGF mediating vascular hyperpermeability and bone destruction within steroid-associated osteonecrotic lesions in rabbits. Rabbits with high risk for progress to destructive repair in steroid-associated osteonecrosis were selected according to our published protocol. The selected rabbits were systemically administrated with either Anti-VEGF antibody (Anti-VEGF Group) or Src inhibitor (Src-Inhibition Group) or VEGF (VEGF-Supplement Group) or a combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…While there have been contradicting reports about the role of Akt in endothelial‐barrier regulation, our recent study has demonstrated the integral role of Akt1 in the long‐term protection of endothelial‐barrier in response to VEGF and Ang‐1 (Gao et al, ). The src family of non‐receptor tyrosine kinases has been implicated in vascular permeability and injury (He et al, ; Paul et al, ). Following ischemia and injury, phosphorylation of Src is highly upregulated causing activation of downstream signaling to induce barrier breakdown and vascular permeability (Esser, Lampugnani, Corada, Dejana, & Risau, ; Ha et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…While there have been contradicting reports about the role of Akt in endothelial‐barrier regulation, our recent study has demonstrated the integral role of Akt1 in the long‐term protection of endothelial‐barrier in response to VEGF and Ang‐1 (Gao et al, ). The src family of non‐receptor tyrosine kinases has been implicated in vascular permeability and injury (He et al, ; Paul et al, ). Following ischemia and injury, phosphorylation of Src is highly upregulated causing activation of downstream signaling to induce barrier breakdown and vascular permeability (Esser, Lampugnani, Corada, Dejana, & Risau, ; Ha et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, periosteal lamellar bone deposition occurs much more slowly, in agreement with a progression of melorheostotic lesions over years . Periosteal new bone formation is often viewed as a physiological response to focal insults or systemic condition such as infections, hemorrhages, inflammations (periostitis), osteonecrosis, tumor processes, and malign neoplasms such as Ewing's sarcoma or Caffey's disease . In fact, so‐called “periosteal reactions” occur widely and represent a rather nonspecific mechanism to maintain bone strength, counteracting the effects of cortical lysis or endocortical bone loss by forming a bridge over damaged cortical area .…”
Section: Discussionmentioning
confidence: 96%
“…(44,46,47) Periosteal new bone formation is often viewed as a physiological response to focal insults or systemic condition such as infections, hemorrhages, inflammations (periostitis), osteonecrosis, tumor processes, and malign neoplasms such as Ewing's sarcoma or Caffey's disease. (13,(48)(49)(50)(51) In fact, so-called "periosteal reactions" occur widely and represent a rather nonspecific mechanism to maintain bone strength, counteracting the effects of cortical lysis or endocortical bone loss by forming a bridge over damaged cortical area. (13) Activating MAP2K1 mutations lead to highly proliferative osteoblasts, poor matrix mineralization, accelerated bone remodeling, and highly increased osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Src-activation is regulated by a number of different signals, including VEGF-A receptor actions. An increase in Src phosphorylation during the acute phase of ischemia is associated with VEGF-induced vascular permeability [ 33 , 88 , 89 ]. Src activation then returns to basal levels within the first day, before a second increase occurs 3–7 days after reperfusion [ 33 ].…”
Section: Vegf-a In the Prevention And Therapy Of Strokementioning
confidence: 99%